An Ordinance to regulate the paving and repairing, and to prevent obstructions in the streets of Jersey City, Title IV, Miscellaneous Provisions, § 7 (28 July, 1843). - (:unkn) unknown (General Publisher, 1843)
No person shall, within this city, fire or discharge any gun, pistol, cannon or fowling-piece, or other fire-arms, unless in defence of his property or person, nor let off any squibs, crackers, or other fireworks, unless by permission of the city authorities, under the penalty of five dollars for each and every offence."
--
Keywords: DISCHARGE